A Survey on Product of Smart Service System - Moh. Roufiq Azmy (APIC, 2019)
Smart service is a new value that results from a collaboration between service providers and service users. Company as a service provider transformed not only provide a physical product, but also provide services. We conducted this research to integrate knowledge between smart products and smart service systems. The conceptualization of smart products is done by conducting a literature study of previous research. It is used to obtain the characteristics of smart products on smart service systems. This research also presents various topics and research focus in the context of products on smart service systems by including several smart service system implementations and illustration of smart product.